Perkembangan Majalah Simba di SMA Negeri 1 Bas - Siska BR Damanik; Hendra Naldi; Etmi Hardi (Jurusan Sejarah FIS UNP, 2019)
This research is the study of the history of the press to describe the development of an existing school magazine at a school inthe Agam, that derived from SMA Negeri 1 Baso which already exists since 2006 up to the last on 2018. This research includes the research of history, and therefore this research follows the history of the method are: (1) heuristic are searching and collecting information from primary and secondary sources, (2) criticism of sources including internal and external criticism, that is whit a test of the authencity of the source or specified materials, (3) interpretasion which interprets activity data that has been collected and (4) historiography is stage presentation of research results in the form of scientific work. The results of this research show that the magazine Simba started in 2006, originally created by teachers in SMA Negeri 1 Baso. The magazine started to grow, not only in the school environment but also to other schools in the vicinity of SMA Negeri 1 Baso, government institutions and agencies in the District of Agam. The developments carried out namely by upgrading the existing writings in the magazine, conducting such visits to the home of puisi Taufik Ismail and conducts training in extracurricular writing in SMA Negeri 1 Baso